Correction of Thumb Duplication: A Systematic Review of Surgical Techniques - Miller, Robert; Kaempfen, Alexandre; Moledina, Jamil; Sivakumar, Bran; Smith, Gill; Nikkhah, Dariush (Journal of Hand and Microsurgery, 2019)
Surgical intervention for thumb duplication can be divided into three categories: simple excision of the accessory thumb, excision of the accessory thumb with reconstruction from available “spare parts,” and combining the two thumbs into one, as described by Bilhaut. This prospectively PROSPERO registered systematic review evaluates the overall, aesthetic and functional outcomes for the latter two options (reconstruction from spare parts vs. combining two thumbs into one), aiming to facilitate evidence-based decision making when addressing thumb duplication and direct future research. The review was performed in accordance with the Cochrane Handbook of Systematic Reviews and PRISMA statement. Embase, PubMed, Medline, and Cochrane databases were systematically searched. Studies offering comparisons of techniques were included. Risk of bias was assessed using the Risk of Bias In Non-randomized Studies—of Intervention tool. The quality of the evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation. Ten retrospective observational studies were included. Data did not consistently allow analysis by procedure type. Four studies reported similar overall outcomes between techniques, while two specifically reported poor overall outcomes for the Bilhaut procedure. Two studies reported comparatively worse aesthetic outcomes for the Bilhaut procedure with four studies reporting comparatively improved functional outcomes for this procedure. Overall, interpretation of outcomes was challenging with no patient-reported outcome measures used. The quality of the evidence was universally “very low” due to all studies being at risk of methodological bias. Based on the available evidence, surgical techniques for thumb duplication correction appear comparable regarding overall outcome. There is limited evidence suggesting reconstruction with spare parts offers superior aesthetic outcomes at the expense of stability. The level of evidence is III.
Keywords: thumb duplication; congenital upper limb anomaly surgery; systematic review